Integrated Marketing Chain Pattern of Smallholder Rubber Commodities in The Southern Region of Papua Province, Indonesia - Simatupang, David Oscar; Wambrauw, Ludia T; Fachrizal, Riza; Redu, Silas Tanggu; Riza, Abdul Rizal; Akbar, Akbar (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Smallholder plantations drive economic growth, provide livelihoods, and support conservation, such as rubber, coffee, and cocoa widely cultivated, including rubber in Papua since the colonial era. This research aims to analyze rubber cultivation's history, development, and challenges in Southern Papua and identify strategies to optimize rubber commodities' supply chain and marketing. The study used qualitative and quantitative approaches, including historical data analysis, interviews with farmers and traders, and analysis of rubber prices from 2009 to 2016. The data are analyzed using the QSPM method to determine strategic priorities based on internal and external factors. The results show that since 1969, rubber development in the region has been facilitated by Catholic missionaries, who played a key role in education and the distribution of rubber seedlings. However, the global decline in rubber prices since 2013 has reduced farmer incomes, with many halting rubber sheet production. Supply chain barriers, such as difficult transportation and a lack of partnerships between farmers and traders, further exacerbate the situation. To address these challenges, the research recommends several strategies. In the short term, rubber plantation rejuvenation and strengthening partnerships between farmers and traders are needed. In the medium term, strengthening cooperatives and financial institutions and supporting production and marketing should be prioritized. In the long term, new processing machinery should be introduced, and medium-scale rubber processing factories should be established—rubber plantations in Merauke face price fluctuations, transportation issues, and weak partnerships. The research suggests rejuvenating plantations, strengthening cooperatives, and building processing factories to improve sustainability.